Water quality monitoring using machine learning and Internet Of Things (IoT) - Rahman, Naveed; Nir, Riaz Uddin Ahmed; Tithi, Saila Hasan; Shupti, Baishakhi Rani Das (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.